Cholesteryl myristate conformation in liquid crystalline mesophases determined by neutron scattering. - Burks, C (1981)
The possible involvement of cholesteryl ester states in the development and persistence of atherosclerosis and the transport and storage of cholesteryl esters has led to questions concerning the organization and conformation of cholesteryl ester molecules in both pure phases and membranes. The experiments we report here were designed to measure the distance between the center of mass of the fatty acyl terminal methyl group and the center of mass of the three-carbon branched terminus of the cholesterol moiety at the opposite end of the molecule. The distance obtained is thus a gauge of cholesteryl ester conformation through the conformational range from a completely extended conformation to a U-shaped conformation. Neutron scattering experiments on partially deuterated samples of pure cholesteryl myristate in the crystalline, smectic, cholesteric, and isotropic phases indicate that the molecule is extended in each of these states. A discussion of specific molecular models consistent with these results and extension of these conclusions to other cholesteryl esters is included.